Gadolinium-doped whitlockite/chitosan composite scaffolds with osteogenic activity for bone defect treatment: In vitro and in vivo evaluations - Xiao, Fei; Shi, Jingjing; Zhang, Xinhai; Hu, Min; Chen, Kangming; Shen, Chao; Chen, Xiaodong; Guo, Yaping; Li, Yang (Frontiers in Bioengineering and Biotechnology, 2023)
Reducing the incidence of bone defects caused by trauma and other primary diseases is an urgent task in modern society. In the present study, we developed a gadolinium-doped whitlockite/chitosan (Gd-WH/CS) scaffold and assessed its biocompatibility, osteoinductivity, and bone regeneration capacity for the treatment of calvarial defect in a Sprague-Dawley (SD) rat model. The Gd-WH/CS scaffolds possessed a macroporous structure, with a pore size ranging 200–300 μm, which facilitated the growth of bone precursor cells and tissues into scaffold. Results of cytological and histological biosafety experiments showed that both WH/CS and Gd-WH/CS scaffolds were non-cytotoxic to human adipose-derived stromal cells (hADSCs) and bone tissue, which demonstrated the excellent biocompatibility of Gd-WH/CS scaffolds. Results of western blotting and real-time PCR analysis provided a possible mechanism that Gd3+ ions in the Gd-WH/CS scaffolds promoted the osteogenic differentiation of hADSCs through the GSK3β/β-catenin signaling pathway and significantly upregulated the expression of osteogenic related genes (OCN, OSX and COL1A1). Finally, in animal experiments, SD rat cranial defects were effectively treated and repaired with Gd-WH/CS scaffolds due to its appropriate degradation rate and excellent osteogenic activity. This study suggests the potential utility of the Gd-WH/CS composite scaffolds in treating bone defect disease.